Healthcare informatics : improving efficiency and productivity - Kudyba, Stephan, 1963- (CRC Press, 2010)
Incorporating information technologies and information management, this work describes evolving areas of efficiency in the healthcare industry due to healthcare informatics enhancements. It discuses innovative information systems and their functionality, and business intelligence in healthcare and the use of analytics and information management.